Supply chain efficiency of Tomato in Kathmandu valley - Bhandari, Hemlal; Bhandari, Thaneshwar; Timsina, Krishna Prasad; Panta, Hari Krishna (Journal of Agriculture and Natural Resources, 2021)
Past studies kept attention on the supply side or value chain aspects of tomato but not kept attention to the supply chain efficiency. To measure supply-side efficiencies in tomato sub-sector, this survey research organized an interview schedule with the randomly selected eighty households in Kirtipur, Chandragiri, Changunarayan, and Godawori municipalities of Kathmandu valley during April to June 2018 with semi structured questionnaire. Study estimated NRs 8,26,144/ha as net profit of tomato grown under tunnel was nearly 44% higher compared to open field condition. Further five types of marketing channels prevailed for tomato market were; channel first (producer-retailer-consumer), channel second (producer-wholesaler-retailer-consumer), channel third (produce-cooperative-retailer-consumer), channel fourth (producer-collector-wholesaler-retailer-consumer) and channel fifth (producer-wholesaler-processor-wholesaler-retailer-consumer) but most dominant was the fourth one since 45% of the fresh tomato supplied through it especially to save time and avoid all possible drudgery in the market. The marketing margin per kilogram of tomato was the lowest (NRs.16.55) in the third channel and the highest (NRs. 39.2) in the fifth channel while the highest market efficiency was 1.27 for the third channel. The producer’s share was highest for the third channel (66.33%) and lowest for fifth channel (39.88%). followed by 1st channel (63.72%) and lowest in 5th channel (39.88%). In order to promote a coordinated and most efficient supply chain, the study suggested the most dominant, low marketing margin and highly efficient supply channel for tomato so that tomato producers would get a high share. Rather than a private one, either group marketing or cooperatives are suggested to involve in fresh tomato marketing.